The Effect of Gemini AI Usage on the Information Literacy of Students in the Library and Information Science Study Program - Sindy Berliana Putri; Marlini Marlini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid advancement of artificial intelligence (AI), particularly generative AI technologies such as Gemini AI, has transformed how students access and use information in academic contexts. Although these technologies offer efficiency and convenience, concerns remain regarding students’ ability to critically evaluate the credibility of AI-generated information. This study aims to examine the effect of Gemini AI usage on the information literacy of students in the Library and Information Science Study Program at Universitas Negeri Padang. A quantitative approach with a descriptive and associative design was employed. The population consisted of 258 students, from which 72 respondents were selected using purposive sampling. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics, product-moment correlation, and simple linear regression with IBM SPSS. The findings indicate that Gemini AI usage has a positive and significant effect on students’ information literacy, with a significance value of 0.002 < 0.05. The coefficient of determination (R² = 0.130) shows that Gemini AI usage contributes 13% to students’ information literacy, while the remaining variance is influenced by other factors. Descriptively, students demonstrated strong abilities in identifying and accessing information; however, limitations were found in their ability to critically evaluate the accuracy and credibility of AI-generated content. This study concludes that Gemini AI usage can enhance students’ information literacy but does not fully support critical evaluation skills. The findings contribute to the literature on AI-assisted information behavior and imply the need to integrate AI adoption with the strengthening of critical and evaluative competencies in higher education.